SiO maser emission as a stellar line-of-sight velocity tracer in the Bulge Asymmetries and Dynamical Evolution (BAaDE) survey. Issue Volume 14:Issue S353(2019) (June 2019) - Stroh, Michael C.; Pihlström, Ylva M.; Sjouwerman, Loránt O.; Lewis, Megan O.; Claussen, Mark J; Morris, Mark R.; Rich, R. Michael; ,
Abstract: The Bulge Asymmetries and Dynamical Evolution (BAaDE) survey aims to explore the complex structure of the inner Galaxy and Galactic Bulge, by using the 43 GHz receivers at the Karl G. Jansky Very Large Array (VLA) and the 86 GHz receivers at the Atacama Large Millimeter/submillimeter Array (ALMA) to observe SiO maser lines in red giant stars. The goal is to construct a sample of stellar point-mass probes that can be used to test models of the gravitational potential, and the final sample is expected to provide at least 20, 000 line-of-sight velocities and positions. A possible bias between the VLA and the ALMA SiO maser lines is explored, and the 86 GHz SiO line-peak velocities agree using either of the four sampled lines. Additionally, the SiO maser velocities agree with the OH maser derived velocities.